HUBUNGAN ANTARA PERAN KONSERVASI TERHADAP SUSTAINABLE DEVELOPMENT GOALS (SDGs) - Triardianti, Annisa; Nugraheni, Nursiwi (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2024)
Development is a process of continuous change towards better conditions based on certain goals. The Environmental Conference in Stockholm in 1972 is said to be the initial milestone for the start of sustainable development. It can be concluded that the link between the National Medium Term Development Plan (RPJMN) and the Sustainable Development Goals (SDGs) lies in the same main vision and mission to improve human life specifically for Indonesia, which is to improve the welfare of all people through Indonesia's participation in realizing the SDGs which are considered important to support development in Indonesia. This research uses a literature study or literature review method. A literature review itself is a comprehensive overview of research that has been conducted on the same topic to show readers what is already known about the topic and what is not yet known, to find rationale for the research that has been carried out or for ideas for further research.